2016
DOI: 10.1002/cyto.b.21487
|View full text |Cite
|
Sign up to set email alerts
|

Elevated IL‐17A and IL‐22 regulate expression of inducible CD38 and Zap‐70 in chronic lymphocytic leukemia

Abstract: IL-22 is elevated and associated with CD38 and Zap-70 expression in patients with CLL. No significant correlation was found between expression of CD38 and increased levels of IL-17A, negative expression of ZAP-70 showed a significant association with increased levels of IL-17A. © 2016 International Clinical Cytometry Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…High IL-22 concentrations and the elevated expression of CD38 may be implicated in the synergetic stimulation of genes involved in proliferation and programmed cell death. Elevated levels are connected with poor outcome in B-CLL patients [182], and it has been reported as a prognostic biomarker in cancers [183,184].…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 99%
“…High IL-22 concentrations and the elevated expression of CD38 may be implicated in the synergetic stimulation of genes involved in proliferation and programmed cell death. Elevated levels are connected with poor outcome in B-CLL patients [182], and it has been reported as a prognostic biomarker in cancers [183,184].…”
Section: Effects Of Cytokines On the Onset Progression And Complicamentioning
confidence: 99%
“…It has been reported that the PBMCs of CLL patients had higher levels of IL-17A and IL-22 mRNA expressions compared with healthy subjects. Moreover, the IL-17A and IL-22 plasma levels were significantly higher in CLL patients compared with control group among Iranians [43]. IL-1β is a pro-inflammatory cytokine that promotes the B cells and lymphocytes proliferation.…”
Section: Inflammatory Factors and Immune Responsementioning
confidence: 90%
“…Endocan overexpression at either messenger ribonucleic acid (mRNA) or protein level have been observed in pituitary adenoma (9,10), gastric cancer (11), bladder cancer (12), non-small cell lung cancer (13), colorectal cancer (14), glioblastoma (15), renal cell carcinoma (16), hepatocellular carcinoma (17), squamous cell carcinoma of head and neck (18,19), pancreatic neuroendocrine tumor (20) and ovarian cancer (21). It is generally accepted that Endocan overexpression is associated with aggressive progression and poor outcomes of tumors (22).…”
Section: Introductionmentioning
confidence: 99%